Development of a Network Management System for HFC networks - Roinila, Joni (fi=Turun yliopisto|en=University of Turku|, 2018)
Traditionally network management has been very laborious. Errors in cable networks are hard to pin point to an exact point and usually field technicians are needed to repair these errors and perform other installations. Human labor is always prone to mistakes which lead to unnecessary truck-rolls, more errors, and higher loss of profits. As the number of network devices as well as their complexity are increasing, more technical problems can occur such as configuration faults, errors in hardware or changes in the overall system that require reconfiguration of the devices. More devices naturally mean more maintenance work for field technicians which mean more costs to the company. This thesis presents improvements to network management systems particularly in HFC networks (Hybrid Fiber-Coaxial) to reduce required manual labor and operational costs to the network operator. A unified big data based solution is proposed along with proactive network maintenance (PNM). DOCSIS 3.1 (Data Over Cable Service Interface Specification) features bring many powerful tools to the table, mainly related to the OFDM (Orthogonal Frequency-Division Multiplexing) downstream signals and OFDMA (Orthogonal Frequency-Division Multiple Access) upstream signals. Bringing intelligence to the network, such as self-adjusting amplifiers, manual labor can be drastically reduced. For comprehensive understanding of the solutions proposed, HFC network and its components, DOCSIS standard, and network management in general are discussed in this thesis as well.